PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS XI MIA SMAN 2 PARIAMAN - HAFNIDA SARI (Departemen Matematika, 2018)
The mathematic concept comperehension is the gool/objective of mathematic learning which has important rolein mathematic learning. The fact,the students’comprehension of mathematic concept at grade XI MIA of SMAN 2 Pariaman are still considered low. It has beenshown from the result of daily examination of interesting mathematic in which just a few number of studentswho can achieved he minimum standard score (KKM), namely the score should be 75. It is caused by the model of learning which is used by the teacher has not increased yet the students’ comprehension of mathematic concept. The solution of this problem is by applying the cooperative learning model type TTW. This research showed that there were the differences of students’ comprehension on mathematic concept, in which students who learned by using cooperative learning model type TTW ishigher than the students who learned by using direct learning model. It can be seen from the differences of mean scores of student who taught byusing cooperative learning model type TTW and they are who taught byusingdirect learning model, namely 17.68 and 15.86 with the highest score was 24. Keywords: Mathematic Concept Comperehension, Cooperative Learning ModelType TTW